(untitled) (Bangladesh Journal of Agriculture, 2025)
A field experiment was carried out at the research field of Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Rajbari, Dinajpur (Latitude: 25038 8.9˝ N, Longitude: 88039 5.79˝ E) during rabi season of 2020-21 and 2021-22 to see the response of vermicompost and rice husk ash on the yield of sweet gourd. Five treatments were included in the experiment as T1=100% RCF (Recommended Chemical Fertilizer) + Vermicompost 3 t/ha, T2=100% RCF+ Rice husk ash 2 t/ha, T3= 100% RCF+ Vermicompost 1.5 t/ha + Rice husk ash 1.5 t/ha, T4=100% RCF +Vermicompost 3 t/ha +Rice husk 1 t/ha, T5=100% RCF + 50% extra potassium. The results revealed that the highest fruit yield was recorded in (T4) 100% RCF +Vermicompost 3 t/ha +Rice husk 1 t/ha followed by that in (T1) 100% RCF+ Vermicompost 3 tha-1 and (T3) 100% RCF + Vermicompost 1.5 t/ha + Rice husk ash 1. t/ha and the lowest in (T5) 100% RCF+50% extra potassium. The highest gross return (Tk. 328500 ha-1), as well as gross margin (Tk. 214600 ha-1), was obtained in (T4) 100% RCF +Vermicompost 3 t/ha +Rice husk 1 t/ha and the lowest gross return (Tk. 151200 ha-1) and gross margin (Tk. 78675 ha-1) were obtained from the treatment (T5) 100% RCF + 50% extra potassium. The highest BCR (2.88) was also obtained from the treatment (T4) 100% RCF + Vermicompost 3 t/ha + Rice husk 1 t/ha combination could be effective for overall productivity and monetary return. Bangladesh J. Agri. 2024, 49(2): 70-78